Penerapan Problem Based Learning (PBL) Melalui Pendekatan Teaching at the Right Level (TaRL) untuk Meningkatkan Hasil Belajar Bahasa Indonesia - Rusgiarty, Meliyanti; Leo Muhammad Taufik; Nita Fatmawati (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2024)
Differentiated learning is an effort to adjust the learning process in the classroom to meet the needs of students. Through the Teaching at The Right Level (TaRL) approach, the grouping of students into differentiated learning is adjusted to the initial ability of students. This research is a type of classroom action research, the subject of the research is class II students totaling 30 students. The purpose of this study is to determine the learning outcomes of students when implementing problem-based learning (PBL) through the teaching at the right level (TaRL) approach in Indonesian Language subjects, capital letters in grade II. The results of the research on the learning outcomes of students in the first cycle got an average score of 82 with classical completeness of 70%, and in the second cycle got an average score of 91.6, with classical completeness of 90%. Based on these results, it can be concluded that the application of problem-based learning (PBL) through the teaching at the right level (TaRL) approach is able to improve the learning outcomes of grade II students in the use of capital letters in Indonesian subjects.